Determination of Diquat Residues in Potato Using Reversed-Phase Liquid Chromatography with Tandem Mass Spectrometry. (22nd November 2019) - Attallah, Emad R; Soliman, Mostafa; Abo-Aly, Mohamed M
Abstract: A simple, modified quick, easy, cheap, effective, rugged, and safe procedure was developed for the determination of diquat in potato using reversed-phase LC coupled with tandem MS(MS/MS) in a total run time of 10 min. Different sample preparation parameters (pH modifier type, sample size, and elevatedtemperature) were tested and optimized. Potato sample was extracted with acetonitrile in the presence of ammonium hydroxide at 80°C. Phase separation was obtained by shaking the extract with magnesium sulfate and sodium chloride, and analysis was done using LC-MS/MS. Matrix-matched standard calculations were used to compensate for matrix-induced suppressionin LC-MS/MS determination. The precision and trueness of the method were determined from recovery experiments on five replicates of spiked blank potato samples at 0.01, 0.05, and 0.1 mg/kg. The range of the obtained recoveries was 74–110%, with RSD values <5% for all the concentrations.